2022
DOI: 10.1111/hsc.13746
|View full text |Cite
|
Sign up to set email alerts
|

Men and loneliness in the Covid‐19 pandemic: Insights from an interview study with UK‐based men

Abstract: Since the onset of the Covid-19 pandemic, the UK, like many countries, has had restrictions on social contact, and injunctions of 'social distancing'. This study aimed to generate new insights into men's experiences of loneliness during the pandemic, and consider the ramifications of these for continued/future restrictions, the easing of restrictions, and the future beyond the pandemic. Twenty qualitative interviews were conducted with men between January and March 2021. A maximum variation purpose sample fram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
4
2
0
Order By: Relevance
“…While our study reinforces prior findings that while COVID both strengthened home‐based family relationships for some and thwarted new romantic partnerships for others (Ratcliffe et al, 2022 ), it goes further in identifying how many younger participants’ longer‐term “life trajectories” were disrupted by lockdown, including education and work‐related relocation plans. This might represent an interruption of late modern work and mobility patterns, with a possible arresting of their socially fragmenting effects (Urry, 2000 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While our study reinforces prior findings that while COVID both strengthened home‐based family relationships for some and thwarted new romantic partnerships for others (Ratcliffe et al, 2022 ), it goes further in identifying how many younger participants’ longer‐term “life trajectories” were disrupted by lockdown, including education and work‐related relocation plans. This might represent an interruption of late modern work and mobility patterns, with a possible arresting of their socially fragmenting effects (Urry, 2000 ).…”
Section: Discussionsupporting
confidence: 86%
“…COVID‐19 exacerbated existing forms of loneliness‐based marginalisation and created new ones, in ways that continued post‐lockdown. It created additional difficulties for those with physical disabilities, some of whom avoided contact because of higher COVID‐19 health risks and anxiety; this reinforces qualitative findings from other studies linking preexisting health issues to increased COVID‐induced anxiety around social contact (Ratcliffe et al, 2022 ). For others, it exposed the “normality” of an absence of contact, and the ease with which they “could be ignored.” It revealed new inequalities in loneliness between those with physical and psychological disabilities and their carers, and those with no such pre‐conditions or responsibilities.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, Kremers et al (2021) found that older Dutch people had a sense of being 'in it together' and adapted to the situation of reduced opportunities for social interaction during the pandemic. As in the present study, both Kremers et al (2021) and Ratcliffe et al (2022) found many people described the impact of restrictions as greater on others than on themselves. Ratcliffe et al (2022) suggest that this may be due to older people wishing to be viewed as knowledgeable of the needs and priorities of others.…”
Section: Disruption Of Normal Lifesupporting
confidence: 78%
“…As in the present study, both Kremers et al (2021) and Ratcliffe et al (2022) found many people described the impact of restrictions as greater on others than on themselves. Ratcliffe et al (2022) suggest that this may be due to older people wishing to be viewed as knowledgeable of the needs and priorities of others. The idyllic account of lockdown similarly was used to acknowledge and mourn inequities in lockdown experiences in A/NZ.…”
Section: Disruption Of Normal Lifesupporting
confidence: 78%